Prognostic Nutritional Index as the Predictor of Long-Term Mortality among HFrEF Patients with ICD. (24th May 2021) - Cinier, G; Hayiroglu, MI; Pay, L; Yumurtas, AC; Tezen, O; Eren, S; Kolak, Z; Cetin, T; Ozcan, KS; Turkkan, C; Ozbilgin, N; Tekkesin, AI; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The benefit of implantable cardiac defibrillator (ICD) in patients with heart failure and reduced ejection fraction (HFrEF) could be limited in a particular group of patients. Low prognostic nutritional index (PNI) indicates malnutrition and pro-inflammatory condition. We sought to investigate the value of PNI in predicting long-term mortality among HFrEF patients with ICD. Methods: Electronic database was searched for identifying patients with HFrEF who were implanted ICD in our institution between 2009 and 2019. Demographic and clinical characteristics of included patients were recorded. PNI was calculated according to the formula: 10 x serum albumin (g/dL) + 0.005 x total lymphocyte count (per mm3). Patients were divided into the quartiles according to PNI values. Differences between the groups were analysed by the log-rank test. A forward Cox proportional regression model was used for multivariable analysis. Results: One thousand and hundred patients were included to the study. The underlying heart failure etiology was ischemic and non-ischemic in 77.3% and 22.7% of patients respectively. Mortality rate in Q1 (5.1%) was considered as the reference. In the unadjusted model the mortality rate was 9.5% [hazard ratio (HR) 1.76, 95% confidence interval (95% CI) (0.92 – 3.38)] in Q2, 10.2% (HR 1.88, 95% CI 0.99 – 3.58) in Q3 and 39.6% (HR 8.12, 95% CI 4.65 – 14.17) in Q4. The same trend was consistent in the age- and sex-adjusted, comorbidities-adjusted and covariates-adjusted models. Conclusion: Among patients who were implanted ICD secondary to HFrEF, lower PNI value predicted all-cause mortality during long-term follow up. This is the first study demonstrating the value of PNI in this population.